In vitro effect of yeast preparations on ruminal methane production - Díaz-Monroy, Byron Leoncio; Castañeda-Caguana, Sandra Isabel (Universidad Pedagógica y Tecnológica de Colombia, 2014)
The aim of this study was to evaluate the effect, in vitro, of Saccharomyces cerevisiae and Levica -25 preparations, viables on ruminal methanogens and methanogenesis. Three treatments were compared: C) Cynodon nlemfuensis (Star grass) as control; S) C. nlemfuensis + S. cerevisiae; and L) Levica 25 + C. nlemfuensis, all with rumen fluid from adult male buffalo. The treatments were evaluated using standard laboratory techniques for microbiological and fermentation indicators at 8, 12 and 24 hours of fermentation, under completely randomized design with 3x3 bifactorial arrangement (3 treatments with 3 sampling times), with 4 replicates for each treatment, and a total of 36 experimental units represented by glass bottles of 100 mL each. We observed statistical differences (P =< 0.01) between treatments and between times assessed for the following indicators: methanogens population, methane gas production, cellulolytic bacteria, total viable bacteria, protozoa and pH. Yeast as a supplement in ruminants diet improves the food usage, increasing the cellulolytic bacteria population and decreasing the methanogenic bacteria population and enteric gas, which is an interesting contribution for mitigation environmental pollution. The yeast Levica -25 was more efficient. We recommend using Saccharomyces cerevisiae and Levica -25 preparations in large ruminants to decrease methanogenesis in the rumen and increase the population of cellulolytic bacteria.